Design and develop new glass bottle recycling system in Kuantan community - Perwira Putra, Iskandar (2012)
Glass is an ideal material for recycling and in some cases can be used repeatedly without any deterioration in its physical properties. In recent years new legislative and fiscal drivers have contributed to increasing the desirability of recycling glass.This has been the case with the glass manufacturing industry , encouraging them to use more recycled glass cullet in place of virgin raw materials. However as with all markets, pressure from legislation can only be effective if the recycled bottle glass supplier can ensure that using recycled materials meet their customers’ quality requirement .Furthermore, the type of glass available for recycling is not the type most demanded by the end market.To meet demands for higher quality cullet, new glass bottle collection system is been developed and introduced to the glassmaking industry that enables processors to improve cullet quality and make production more efficient.The development of new collection system and alternative markets for recycled glass has further contributed to the development of new technologies. Processing technologies have needed to keep pace with the variety of specifications introduced by these new end markets.